A systematic review of a novel alloplast carbonate apatite granules - Nunn, Martha E.; Rudick, Courtney; Nikaido, Masahiko; Miyamoto, Takanari (Frontiers in Dental Medicine, 2024)
The objectives of this study are to provide a systematic review of a novel alloplastic hard-tissue grafting material, carbonate apatite granules (CO3Ap-granules), to provide a clinical case presentation of CO3Ap-granules in periodontal surgery. The following three electronic databases were searched independently by two of the authors (MN) and (CR): National Library of Medicine [MEDLINE (PubMed) and ClinicalTrials.gov], EMBASE (OVID) and the Cochrane Central Register of Controlled Trials (CENTRAL). After searching electronic databases, select journals in periodontics and implantology were also manually searched. Of the 43 studies identified from the systematic review, the following classifications were determined: (1) in vitro studies – 5 studies, (2) animal studies – 28 studies, (3) clinical studies – 7 studies, (4) reviews – 3 studies. Results from selected animal studies and all human studies were summarized. These results demonstrate that the novel alloplast CO3Ap-granules has the potential ability to stimulate new bone formation while CO3Ap-granules simultaneously resorb over time. Replacement of CO3Ap-granules with new bone formation has been shown to be comparable to autogenous bone grafting with one study showing superior results to a bovine-derived xenograft.